Overall care-seeking pattern and gender disparity at a specialized mental hospital in Bangladesh - Nuri, Nazmun Nahar; Sarker, Malabika; Ahmed, Helal Uddin; Hossain, Mohammad Didar; Dureab, Fekri; Agbozo, Faith; Jahn, Albrecht (Materia socio-medica, 2022)
This article was published in the Materia socio-medica [© 2019 Nazmun Nahar Nuri, Malabika Sarker,, Helal Uddin Ahmed, Mohammad Didar Hossain, Fekri Dureab, Faith Agbozo,, Albrecht Jahn ] and the definite version is available at: http://dx.doi.org/10.5455/msm.2019.31.35-39 The Journal's website is at: https://www.ejmanager.com/mnstemps/16/16-1552336392.pdf?t=1647425347